Jealousy and Equilibrium Overconsumption - Dupor, Bill; Liu, Wen-Fang (American Economic Review, 2003)
The idea that the happiness of an individual depends upon the consumption of others is widely viewed as an important feature of our shared social existence. Recent research in finance has used this idea, through consumption externalities, to explore asset-pricing anomalies. Consumption externalities potentially break the link between Pareto optimality and competitive equilibria and open the door for beneficial government intervention (e.g., Lars Ljungqvist and Harald Uhlig, 2000). In this paper, we delineate two effects that a consumption externality may have. An increase in aggregate consumption may: (a) raise the marginal utility of individual consumption relative to leisure, and/or (b) lower an individual’s utility level. We refer to (a) as “keeping up with the Joneses” (henceforth, KUJ), following Jordi Gali (1994), and we refer to (b) as jealousy. Jealousy is a distinct concept from KUJ. Under KUJ, an individual derives greater utility from additional own consumption relative to leisure when others consume more. At the same time, higher per capita consumption holding fixed individual consumption can trigger either jealousy, so that individual utility falls, or admiration, so that individual utility rises. In Section I of this paper, we show that jealousy implies that the laissez-faire equilibrium consumption level is greater than the optimal level. Whether preferences exhibit KUJ is not necessary for this main result. Intuitively, in the presence of jealousy, consumption is similar to pollution. Overpollution exists because individuals do not take into account the cost of polluting on others, not because an increase in economywide pollution makes the return to individual polluting higher. Similarly, overconsumption exists because individuals do not take into account the negative effect of own consumption on jealous others. Things go in the opposite direction when individuals are admiring. In Section II, we consider a functional form that encompasses several existing models. We show that jealousy determines the optimal tax to correct overconsumption and that KUJ is mainly important for asset pricing.